2013
DOI: 10.1186/1756-3305-6-4
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics and host reactions in young foxes following experimental infection with the minute intestinal fluke, Haplorchis pumilio

Abstract: BackgroundInfections with fish-borne zoonotic trematodes (FZT) including the minute intestinal fluke, Haplorchis pumilio, are highly prevalent in Southeast Asia. However, little is known about the infection dynamics and clinical symptoms in the final hosts which include a range of animal species and man. We aimed to generate such information using an experimental model with H. pumilio in foxes.MethodEight commercially bred foxes were each orally infected with 2000 H. pumilio metacercariae. Another three foxes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Prevalence was modelled as a Beta distribution (Table 1 ). The mean and standard deviation of the faecal output of foxes were provided by Nissen et al [ 42 ] so that the fox faecal output ( F 4 ) could be modelled as a log normal distribution (Table 1 ). EPG in foxes by age group ( I 4 j ) was obtained from Saeed et al [ 12 ] and modelled as a Poisson distribution (Table 1 ), with no changes over degrees of urbanization.…”
Section: Methodsmentioning
confidence: 99%
“…Prevalence was modelled as a Beta distribution (Table 1 ). The mean and standard deviation of the faecal output of foxes were provided by Nissen et al [ 42 ] so that the fox faecal output ( F 4 ) could be modelled as a log normal distribution (Table 1 ). EPG in foxes by age group ( I 4 j ) was obtained from Saeed et al [ 12 ] and modelled as a Poisson distribution (Table 1 ), with no changes over degrees of urbanization.…”
Section: Methodsmentioning
confidence: 99%
“…pipiens f. pipiens, even in the original field material) is highly likely to be representative of this form, results from the Brookwood line are more difficult to interpret. The fact that these lines and the additional Wageningen line originating from The Netherlands failed to support full SBV dissemination, however, would suggest that the presence of hybrids in tested populations does not substantially influence vector competence for SBV, in contrast to WNV [ 17 ]. Further studies to examine this issue directly with zoonotic pathogens would be useful in elucidating the potential role that these hybrids might play in arbovirus outbreaks in northern Europe.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that hybridization in Cx . pipiens may, alongside differences in host preference [ 16 ], drive transmission of West Nile virus (WNV; Flaviviridae , Flavivirus ) through hybrids possessing a greater vector competence [ 17 ]. The full characterization of individuals as specific forms or hybrids is therefore becoming an increasing important factor in studies [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Including domestic animals in treatment campaigns would be a major challenge. At least for intestinal FZTs, the short life cycle [54] means that animals should be treated at frequency that is not logistically feasible. Hence farm/pond management [38] including stocking of ponds with black carp could well prove the major intervention to prevent infections in fish and people.…”
Section: Discussionmentioning
confidence: 99%